(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
The research work was conducted to find out the seasonal prevalence and intensity of infestation of the ectoparasites of carps in some ponds of Mymensingh and Bogra districts of Bangladesh. Seven species of parasites viz. Trichodina domerguei, Trichodina reticulata, Chilodonella cyprini, Myxobohts koi, Dactylogiroides tripathi, D. extenswi and D. catlarius were found from 640 fry-fingerlings of silver carp, Hypophthalmicthys mohtrix (Valenciennes), grass carp, Ctenopharyngodon idella (Valenciennes), European carp, Cyprinns carpio (Linnaeus), small carp, Puntius gonionotus (Bleeker), katla, Catla catla (Hamilton), rui, Labeo rohita (Hamilton-Buchanan) and mrigal, Cirrhina mrigala (Hamilton- Buchanan) from different nurseries and rearing ponds of Mymensingh and Bogra districts of Bangladesh during June, 2004 to October, 2005. The overall percentage of infestations in two study areas was the highest (95%) in winter, moderate (48%) in summer and the lowest (34.8%) in the rainy season. The physicochemical parameters of water exerted more or less significant combined effect on the occurrence of parasites. Key words: Ectoparasites infestation, Carps, seasonal prevalence, Physicochemical parameters. Â Â DOI = 10.3329/bjsir.v43i3.1158 Bangladesh J. Sci. Ind. Res. 43(3), 411-418, 2008